The Effect of Profitability and Leverage on Sustainability Report Disclosure: Evidence from Manufacturing Companies Listed on the Indonesia Stock Exchange, 2020–2024 - Bella Fitri Melinia; Rhoma Iskandar; Syukri Hamdi (Goodwood Publishing, 2026)
Purpose: This study investigates the effects of profitability and leverage on sustainability report disclosure among manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2024. Research Methodology: A quantitative descriptive-verificative design was used with secondary data from annual financial and sustainability reports. Profitability was measured by Return on Assets (ROA), leverage by the Debt to Assets Ratio (DAR), and sustainability report disclosure by the Sustainability Report Disclosure Index (SRDI) based on GRI-G4 standards. A purposive sample of 13 manufacturing companies resulted in 65 firm-year observations. Multiple linear regression was applied after classical assumption tests. Results: The simultaneous F-test indicates that profitability and leverage jointly and significantly affect sustainability report disclosures (F = 9.091, p < 0.001, R² = 0.521). Profitability (ROA) shows a significant negative effect (? = ?0.405, t = ?3.873, p < 0.001), while leverage (DAR) shows a significant positive effect (? = 0.177, t = 2.120, p = 0.038). Together, both variables explain 52.1% of the variance in sustainability disclosures. Conclusions: Profitability (ROA) and leverage (DAR) significantly influence sustainability report disclosure (SRDI) in Indonesian manufacturing companies, explaining 52.1% of their variance. Lower profitability and higher leverage are associated with more extensive sustainability disclosures. Limitations: The sample is limited to 13 manufacturing companies, and 47.9% of the variance is influenced by factors not included in the model. Contributions: The findings offer insights into how financial performance and capital structure affect non-financial disclosures, providing practical guidance for managers, investors, and regulators.